2015
DOI: 10.1371/journal.pone.0132684
|View full text |Cite
|
Sign up to set email alerts
|

Association between the Adherence to the International Guidelines for Cancer Prevention and Mammographic Density

Abstract: IntroductionMammographic density (MD) is considered a strong predictor of Breast Cancer (BC). The objective of the present study is to explore the association between MD and the compliance with the World Cancer Research Fund and the American Institute for Cancer Research (WCRF/AICR) recommendations for cancer prevention.MethodsData of 3584 women attending screening from a population-based multicenter cross-sectional study (DDM-Spain) collected from October 7, 2007 through July 14, 2008, was used to calculate a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 39 publications
1
12
0
Order By: Relevance
“…Several studies had evaluated the association between the WCRF/AICR score and breast cancer risk and most, but not all of them have reported a statistically significant reduced breast cancer risk in women following the WCRF/AICR recommendations. When we stratified by menopausal status, we observed this association in postmenopausal women, but not in premenopausal women.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies had evaluated the association between the WCRF/AICR score and breast cancer risk and most, but not all of them have reported a statistically significant reduced breast cancer risk in women following the WCRF/AICR recommendations. When we stratified by menopausal status, we observed this association in postmenopausal women, but not in premenopausal women.…”
Section: Discussionmentioning
confidence: 99%
“…directions between all components of the score and colon and rectal cancer, except for body fatness that was associated with colon but not with rectal cancer, and alcohol intake that was not associated with neither colon nor rectal cancer. Several studies had evaluated the association between the WCRF/AICR score and breast cancer risk and most, 4,5,20,21,25 but not all 6,8,10 of them have reported a statistically significant reduced breast cancer risk in women following the WCRF/AICR recommendations. When we stratified by menopausal status, we observed this association in postmenopausal women, but not in premenopausal women.…”
Section: Cancer Epidemiologymentioning
confidence: 99%
“…This is a cross-sectional multicenter study included in DDM-Spain (Determinants of Mammographic Density in Spain)/Var-DDM (Variability of the Mammographic Density in Spanish Women) research project. More detail regarding the design of the study is provided elsewhere (17,22). Briefly, in Spain, the publicly funded and population-based breast cancer screening network invites all women between 50 and 69 years old (45-69 in some regions) to be screened every 2 years, with attendance rates ranging from 62.9% to 88.0% of its target population, depending on the region (23).…”
Section: Methodsmentioning
confidence: 99%
“…However, the relationship between MD and NSW has only been explored in a previous study with inconclusive results (21). If confirmed, this association could have practical effects: Being MD the leading potentially modifiable intermediate marker for breast cancer, preventive strategies to reduce MD (22) might moderate the excess of breast cancer risk associated to NSW.…”
Section: Introductionmentioning
confidence: 99%
“…Studies on the modulating effects of diet and PA on breast density have been mostly observational and results are mixed. Some studies suggested positive associations with high intake of saturated fatty acids (28,29), proteins and carbohydrates (30,31), alcohol (32)(33)(34)(35), consumption of sweet foods (36), and with the adherence to a Western-style diet (37). An inverse association with fiber and carotenoids (28), vitamin D, and calcium (38,35) emerged in some studies, but these findings were not confirmed by others (39)(40)(41)(42).…”
Section: Discussionmentioning
confidence: 99%